Drosophila Cip4 and WASp define a branch of the Cdc42-Par6-aPKC pathway regulating E-Cadherin endocytosis - Leibfried, Andrea; Fricke, Robert Patrick; Morgan, Matthew J.; Bogdan, Sven; Bellaïche, Yohanns (Current biology, 2008)
Background - Integral to the function and morphology of the epithelium is the lattice of cell-cell junctions known as adherens junctions (AJs). AJ stability and plasticity relies on E-Cadherin exocytosis and endocytosis. A mechanism regulating E-Cadherin (E-Cad) exocytosis to the AJs has implicated proteins of the exocyst complex, but mechanisms regulating E-Cad endocytosis from the AJs remain less well understood. - Results - Here we show that Cdc42, Par6, or aPKC loss of function is accompanied by the accumulation of apical E-Cad intracellular punctate structures and the disruption of AJs in Drosophila epithelial cells. These punctate structures derive from large and malformed endocytic vesicles that emanate from the AJs; a phenotype that is also observed upon blocking vesicle scission in dynamin mutant cells. We demonstrate that the Drosophila Cdc42-interacting protein 4 (Cip4) is a Cdc42 effector that interacts with Dynamin and the Arp2/3 activator WASp in Drosophila. Accordingly, Cip4, WASp, or Arp2/3 loss of function also results in defective E-Cadherin endocytosis. - Conclusion - Altogether our results show that Cdc42 functions with Par6 and aPKC to regulate E-Cad endocytosis and define Cip4 and WASp as regulators of the early E-Cad endocytic events in epithelial tissue.
Gesehen am 08.05.2023